117k views
1 vote
Let f(x) = x2 - 16. Find F-1(x). (1 point)

User Goun
by
5.4k points

2 Answers

6 votes

Answer:

F-1(x) = √(x + 16).

Explanation:

Let y = x^2 - 16

First make x the subject:

x^2 = y + 16

x = √(y + 16)

Now replace x by the inverse f-1(x) and replace y by x:

f-1(x) = √(x + 16).

Note we only take the positive square root otherwise we would not have a function.

User Bastian
by
5.5k points
4 votes

Answer:

See below.

Explanation:


f(x) = x^2 - 16

Replace f(x) with y.


y = x^2 - 16

Switch x and y.


x = y^2 - 16

Solve for y.


y^2 = x + 16


y = \pm√(x + 16)

Replace y with f^(-1)(x).


f^(-1)(x) = \pm√(x + 16)

The relation above is not a function, so the given function f(x) does not have an inverse unless the domain is restricted.

User D V Yogesh
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.